Building Capacity of Interpreting Services in Australian Healthcare Settings: The Use of Video Remote Interpreting during the COVID-19 Pandemic - Karine Bachelier; Marc Orlando (Media and Intercultural Communication: A Multidisciplinary Journal)
Confronted with a crisis of unprecedented scale in the second quarter of 2020, Australian States and Territories had to adopt crisis management strategies to ensure equitable access to services are guaranteed for all communities. In this context, and because face-to-face interpreting was no longer an option for each consultation, clinics, hospitals, and GP practices were urged to resort to remote interpreting, i.e., the use of technologies to gain access to an interpreter. After setting the Australian healthcare interpreting scene against historical milestones, this article discusses the usability of Video Remote Interpreting (VRI) in Australian healthcare settings, the way the demands for this new modality were met, as well as the perceptions of participants involved in remote communication. Findings from a mixed method study are presented and discussed. The data collected through surveys and interviews aimed to identify how and if the use of VRI proved efficient, and if this modality was expected to replace onsite and telephone interpreting and to what extent. The outcomes showed a shift from Telephone Interpreting to Video Remote Interpreting as the preferred remote modality, though onsite interpreting remains the preferred modality of the participants involved in the communication exchange.